A highly sensitive colorimetric and fluorogenic detection of copper(II) ion based on new picolylamine-armed calix[4]arene. (31st March 2023) - Tabakci, Begum; Ozcelik, Egemen; Erdemir, Serkan; Tabakci, Mustafa
Graphical abstract: Highlights: A picolylamine-armed calix[4]arene-based colorimetric and fluorogenic sensor was developed for Cu 2+ . The sensor exhibits good performance for Cu 2+ with low LOD. A sensor with high sensitivity, selectivity, repeatability and stability was developed for Cu 2+ . The sensor exhibits excellent practicability for Cu 2+ detection in real samples. Abstract: In this study, two- and tetra-functionalized with bis(2-picolyl)amine calix[4]arene derivatives (2-PACX and 4-PACX ) were synthesized, and their structures were confirmed by 1 H NMR, 13 C NMR, FT-IR and TOF-MS spectroscopies. Cation sensing behaviors of them were investigated towards several cations such as Fe 2+, Al 3+, Cr 3+, Hg 2+, Mn 2+, Cu 2+, Co 2+, Cd 2+, Zn 2+, Ni 2+, Ag +, Mg 2+, Ca 2+, Li +, Na +, and K + . The results showed that 4-PACX was an effective colorimetric sensor against Cu 2+ ions. The binding constant ( K ) value of the complexation between 4-PACX and Cu 2+ ion was calculated as 4.62x10 8 M −2 and the detection limit value of the sensor as 5.1 μM. Moreover, the fluorescence studies demonstrated that 4-PACX has great fluorogenic sensor potential with 0.16 μM of detection limit. As a result, good yield, large coupling constant with Cu 2+ ion ( K a = 13.972), applicability to aqueous samples, low detection limit, and high sensitivity were some of the advantages of the obtained sensor.